Factors Associated With Dietary Behaviour Among Patients With Type 2 Diabetes Mellitus in Rural Indonesia - Kurnia, Anggraini Dwi; Masruroh, Nur Lailatul; Melizza, Nur; Prasetyo, Yoyok Bekti; Hidayani, Herdianti Nur (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Background. Type 2 Diabetes Mellitus (T2DM) is one of the fastest-growing diseases and most serious major health problems worldwide. Few studies have focused on the association of social support with diabetes-related dietary behaviour. Objective. To examine the relationship between social support and dietary behaviour among patients with diabetes in a rural area of Indonesia. Methodology. This was a descriptive cross-sectional study that included 120 physically healthy patients above 18 years old with type 2 diabetes mellitus for at least 6 months. Data analysis was done using a stepwise regression model. Results. The mean age was 61.97 years (SD = 7.85, range = 52-74); 86.7% of the participants were females. Social support (β = 0.272, p = <0.001), diabetes medications (β = 0.169, p = 0.003), duration of diabetes (β = 0.118, p = 0.0047), and presence of diabetes complications (β = 0.197, p = 0.008) were significant predictors of dietary behaviour and accounted for 34.2% of the variance. Conclusion. Social support, diabetes medications, presence of diabetes complications, and duration of diabetes were associated with improved dietary behaviour. Therefore, social support should be considered when designing dietary interventions for patients with type 2 diabetes mellitus.